Pengembangan Kurikulum Pedidikan Agama Islam (PAI) dalam Menyongsong Era Digital dan Moderasi Beragama - Hidayati, Yusranida; Lutfiah, Izmi; Rahmat, Ilham; Halimah, Siti (Innovative: Journal Of Social Science Research, 2025)
Digital transformation has reshaped the learning paradigm of Islamic Religious Education (PAI), shifting from conventional classrooms to flexible and open virtual spaces. However, the PAI curriculum still faces challenges, such as educators' low digital literacy and the lack of systematic integration of religious moderation values. This study aims to explore curriculum development strategies for PAI that are responsive to the digital era while internalizing Islamic moderation (wasathiyah) values. This research employed a descriptive qualitative approach using library research methods. Data were collected from recent academic literature and curriculum policy documents. The findings indicate that PAI curriculum development requires an integrative strategy: (1) updating curriculum content to address current digital issues, (2) strengthening technology-based pedagogy, and (3) internalizing moderation values through reflective and collaborative learning activities. Through this approach, the PAI curriculum serves not only as a vehicle for transmitting Islamic values but also as a strategic instrument for shaping digitally literate, moderate, and socially adaptive Muslim generations.